Green financing as a mechanism for advancing sustainable energy projects - International experiences with reference to Algeria- - Ramdan, Imene; Harmouche, Imane; Mekimeh, Sabri (Finance and Business Economies Review, 2019)
This study aims at highlighting the importance of investing in sustainable energy as one of the most important alternatives to achieving sustainable development in the direction of the green economy, as well as the importance of investing in green energy technology which also plays a major role in developing energy and rationalizing its use to protect the environment. The study also aims to identify the mechanisms of green financing in the field of sustainable energy by presenting some successful experiences of some countries in this field, in addition to addressing the reality of Algeria's interest in sustainable energy projects and sources of funding, So far, with the latter coming up with some suggestions on the subject